.5 log4 5^2 = log4(5)
2(3 log4 5 - 2 log4 5 ) = 2 log4 5
so we have
that might be the answer you are looking for but if you need a number
4^x = .2 ?
x ln 4 = ln .2
x = 1.39/-1.61
= - .863
I have to condense it... thanks for your help
1/2log base 4 25-2(3logbase4 5-log base 4 25)
= 1/2 log4 25 - 2(3log4 5 - log4 25)
= log45 - 2(log4125 - log425)
= log45 - 2(log4(125/25)
= log45 - 2log45
my teacher has a different answer... she has log base 4(1/25).
Well, I think log4 (1/5)
I got -1 log4 5
she got -2 log4 5
one of us subtracted wrong or something
However Reiny and I agree exactly, so the odds are in our favor :
my teacher got log base 4 (1/125) and it's a quiz review sheet, and all the math teachers look over it... sooo... I get how to simplify the 1/2 part but how do i condense the parenthesies
Well, Miley, if you typed your question correctly, then your teacher is wrong.
Even though both Damon and I did it slightly differently, we came up with the same answer.
I evaluated your original expression the way it stands on my calculator, and got the same result as our answer at the end.
By the way, your teacher and I both said
-n log4 x = log4 x^-n = log4 (1/x^n)
which is how we converted the negative log to positive
can you please show me how to condense -2(3logbase 4 5-log base 4 5), thanks:)
I do not know what to say. Reiny and I did the parentheses quite different ways and both got the same answer.
Can you please break it down step by step and show me how you did it! thanks:)
You have two ways to condense the inside the parentheses up there
I did it by saying log 25 = 2 log 5
Reiny did it by saying
log 125 - log 25 = log (125/25) = log 5
what happen to the base 4?
What I wrote a few minutes ago is true for any old base so I left the 4 out
ohh okay thanks
-2(3logbase 4 5-log base 4 5)
Hey, that is not what you wrote in the original question
that is just -2 (2 log4 5)
-4 log4 of 5
log4 5 - 4 log4 5
= -3 log4 5
= log4 (1/5^3)
= log4 (1/125)
oh my bad, sorry. wait how did you get rid of the negative two on the outside?
-2(2 log) = -4 log
Uh...I'm posting this one on gothomework.tk